PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TERHADAP EKUITAS PADA PERUSAHAAN KEUANGAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Tia Novira Sucipto (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
This study aims to determine: (1) the effect of tax planning partially on equity in financial companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019, (2) the effect of tax expenses partially on equity in financial companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019, and (3) the effect of tax planning and tax expenses Simultaneously on equity in financial companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The population in thisstudy were all financial companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019 as many as 45 companies. The sample in this study were 16 Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange which were in accordance with the sampling criteria. Determination of the sample in this study using purposive sampling, the total sample collected was 75 financial statement data for the 2017-2019 period from 25 samples of financial companies in the banking subsector listed on the Indonesia Stock Exchange (IDX). Data collection methods used are documentation studies. The data analysis technique used is descriptive statistics, classical assumption test, and multiple linear regression analysis with partial test,simultaneous test, and coefficient of determination, with the help of the IBM SPSS version 25 program. The results of this study indicate that tax planning partially has a effect on company equity, tax expenses partially has a effect on company equity, as well tax planning and tax expenses simultaneously have a effect on equity company